A comparison between male judo-kas and karate-kaswithin body composition and physical fitness - Satpal Yadav (Selcuk University, 2014)
The purpose of the study was to compare the body composition and physical fitness between male judo-kas and karate-kas. The subjects were selected from the male Judokas and Karatekas of different colleges and training centers, who had participated last 2 years at Punjab state level competitions for this study. Ten (10) male Judokas and Karatekas from three different weight categories namely light weight, middle weight and heavy weight were selected as the subject for the study. Selected body composition such as Standing Height, Weight, HumerusBiepicondylar, Wrist Diameter, Femur Biepicondylar, Ankle Diameter, Upper arm Circumference, Forearm Circumference, Thigh Circumference, Calf Circumference, Bicep Skinfold, Forearm Skinfold, Suprailiac Skinfold, Subscapular Skinfold, Thigh Skinfold, Calf Skinfold  and Physical fitness variables such as 50 meter Dash, Shuttle Run, Shot Put, 600 yards Run or Walk and Bend and Reach Test were presented to compare the male Judokas and Karatekas from three different weight categories namely light weight, middle weight and heavy weight. To see the significant difference of selected body composition and physical fitness variables among the male Judokas and Karatekas from three different weight categories namely light weight, middle weight and heavy weight, the analysis of "mean, standard deviation and t test" was applied at .05 level of significance. The judokas are found to be taller and having greater diameters and circumferences and leaner in all skinfolds except suprailiac skinfold. The karatekas found to be heavier and having greater upper arm and forearm circumferences and leaner in suprailiac skinfold than judokas. However, the Judokas have greater bone mass, muscle mass and less fat percentage than Karatekas. Further Judokas have more speed, coordinative ability and endurance than Karatekas.